2012
DOI: 10.4269/ajtmh.2012.11-0552
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Rhesus Plasmodium cynomolgi Model to Screen for Anti-Hypnozoite Activity of Pharmaceutical Substances

Abstract: Abstract. There remains a need for new drugs to prevent relapse of Plasmodium vivax or P. ovale infection. The relapsing primate malaria P. cynomolgi has been used for decades to assess drugs for anti-hypnozoite activity. After sporozoite inoculation and blood-stage cure of initial parasitemia with chloroquine, rhesus macaques were treated on subsequent relapses with chloroquine in conjunction with test regimens of approved drugs. Tested drugs were selected for known liver or blood-stage activity and were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 9 publications
3
47
1
1
Order By: Relevance
“…Based on AFRIMS historical data, daily doses of 1.3 and 1.78 mg/kg/day have been 100% curative, preventing further relapse (14). Doses of 0.6 mg/kg/day have given variable results and appear to approximate ED 50 , while doses of 0.3 mg/kg for 7 days have been ineffective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on AFRIMS historical data, daily doses of 1.3 and 1.78 mg/kg/day have been 100% curative, preventing further relapse (14). Doses of 0.6 mg/kg/day have given variable results and appear to approximate ED 50 , while doses of 0.3 mg/kg for 7 days have been ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…For the P. cynomolgi malaria radical cure study, 10 rhesus macaques were allocated to 5 groups of 2 animals each to receive 7 daily doses of (ϩ)-or (Ϫ)-PQ base at 1.3 or 0.6 mg/kg/day in combination with the chloroquine base at 10 mg/kg/day, with two of the animals receiving chloroquine alone as negative controls. Animals were infected with P. cynomolgi and treated to prevent relapse using a previously described method (14,15). Animals received 1 ϫ 10 6 P. cynomolgi sporozoites intravenously on study day 0 and were treated when parasitemia reached Ն5,000 blood-stage parasites on peripheral blood film.…”
Section: Methodsmentioning
confidence: 99%
“…The proof of concept in vivo for the anti-hypnozoiticidal potential of a preclinical molecule is obtained if a molecule demonstrates anti-relapse activity (out to 100 days) in the gold standard preclinical model, the P. cynomolgiinfected rhesus model. 66 The ultimate validation will finally take place in human clinical trials after a full preclinical safety and pharmacokinetic package has been obtained. The key radical cure human models in this case are a Phase II clinical study in patients with confirmed P. vivax monoinfection and with a primary endpoint measured as the percentage of relapse-free efficacy at 6 months post initial dose similar to that used in the tafenoquine DETECTIVE trial 38 and/or a Phase II 'out of transmission' model where Indonesian soldiers who have spent up to 12 months in P. vivax endemic areas (Papua) are returned to their malaria-free base (Java) and given new anti-relapse agents and followed-up over the course of 12 months.…”
Section: 62mentioning
confidence: 99%
“…PZA, along with INH and RIF, forms the cornerstone 101 of modern TB therapy that enables treatment of drug-susceptible 102 TB within 6 months. It is currently being considered as part of 103 future regimens in combination with bedaquiline (TMC207), the 104 bicyclic nitroimidazole (PA-824) and moxifloxacin, and these are 105 now in phase 3 trials [11]. These new drug combinations are 106 expected to shorten the treatment period for drug-susceptible TB, 107 as well as MDR and XDR TB.…”
mentioning
confidence: 98%
“…108 Notably, PZA also inhibits the quiescent malaria parasite in the 109 mouse model [11] and is also active against Escherichia coli 110 ampicillin-tolerant persisters [12]. Although there is considerable 111 recent interest in developing antibiotics targeting persisters [13-112 15], PZA is the only prototype persister drug so far that has been 113 shown to improve the treatment of a persistent infection.…”
mentioning
confidence: 99%